Study of Special Employment Programme Design Schedules and Instructions - Planning Commission (Planning Commission, 1975)
During the Fourth Five Year Plan period, various efforts were made to supplement the employment objectives of the Five Year Plans through Special Employment Programmes The need for such programmes was highlighted, by the situation coextensive unemployment. of technically trained and other educated persons, as well as the continuing income of the poorest among the rural labouring classes These Programmes can thus be classified into those meant for the educated and the un educated ,or as for the urban and rural populations, or as having mainly developmental objectives or redistributive objectives.
Programme Evaluation Organisation Planning Commission Government of India